Gaya Kepemimpinan di Lingkungan Kerja dan Organisasi Pada MAN Kota Solok - Wardani, Kurnia; Hendriani, Suswati (Jurnal Pustaka Cendekia Pendidikan, 2023)
The leadership style applied by the Principal of Man Kota Solok currently has three leadership styles. Democratic leadership style can be seen in the deliberations held for decision-making related to teachers and employees. The autocratic leadership style is applied when it comes to financial management. Then the free leadership style (laissez faire) is applied when daily activities are carried out. However, in general, the leadership style applied is a free (laissez faire) but bound leadership style. Although in some cases implementing autocratic and democratic leadership styles. This is done because the people we face and also the problems are also different, then the situations and conditions we face are also different. So to complete it the principal uses these three leadership styles. In addition to strengthening the leadership style applied, the leader also applies his leadership functions, namely instructive, consultative, participation, delegation, and control. And good and proper leadership is one of the important assets that must be owned in the Man City Solok Regional Environment. This has encouraged school principals in the city of Solok to carry out activities in the form of training and development in improving the quality of leadership. The realization of realizing proper and correct leadership is proven by the existence of leadership training activities in the form of education and training (Training) provided by the Regional Government of Solok district. As well as organizations in Solo City Man have a goal of profitability and developing in a better direction. Another similarity, the school consists of people who have different goals. the management at the school has its own goals that are aligned with organizational goals because the main goal is how the Man Kota Solo school can progress and develop.